Homotopy perturbation method for biological species living together - Biazar, Jafar; Ayati, Zeinab; Partovi, Masoome (International Journal of Applied Mathematical Research, 2012)
In this paper, Homotopy perturbation method has been used for solving systems of nonlinear integro-differential equations governing on the problem of results reveal that the method is very effective and simple. The results of homotopy perturbation method are of high accuracy. The example is presented to show the ability of the method.